The Ability of Entomopathogenic Fungus as Biocontrol of Periplaneta americana - Anggita Rahmi Hafsari; Ayu Nur Hidayah (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2022)
Periplaneta americana (cockroach), are well-known pests that not only contaminate food with feces and germs that can cause food poisoning, but also transfer bacteria, fungus, and other dangerous microbes. Chemical pesticides are harmful to both the environment and individuals when used in excess. The natural balance has been disrupted, resulting in resistant pests, predatory threats, parasitic threats, fish, birds, and other animals. The objective of this research is to see the ability of an entomopathogenic fungus as a cockroach biocontrol agent. This research conducted with experimental research with ten treatments and three repetition. The variation are, K(-) only distilled water, K(+) synthetic pesticides, Botrytis sp., Mucors sp., Acremoniums sp., Rhizopus sp., Moniliella sp., Chaetomium sp., Nigospora sp., and Aspergillus sp. A one-way Completely Randomized Design was used to examine them (CRD). With a cell count of 2.35 x 108 CFU/ml, Rhizopus sp. was able to achieve a mortality rate of cockroach by 66.6 percent.